2016
DOI: 10.1038/srep39595
|View full text |Cite
|
Sign up to set email alerts
|

Cognitive control activity is modulated by the magnitude of interference and pre-activation of monitoring mechanisms

Abstract: The Simon task is used to study interference from irrelevant spatial information. Interference is manifested by longer reaction times when the required response –based on non-spatial features- is spatially incompatible with stimulus position. Interference is greater when incompatible trials are preceded by compatible trials (compatible-incompatible sequence) than when they are preceded by incompatible trials (incompatible-incompatible sequence). However, the relationships between spatial attention, interferenc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
12
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(12 citation statements)
references
References 57 publications
0
12
0
Order By: Relevance
“…The MFN/N450 peaks at ~450 ms in visual Stroop tasks (Tillman & Wiens, 2011; West & Bailey, 2012). It shows both base rate and sequence effects and is thought to reflect conflict monitoring (Cespón, Galdo-Álvarez, & Díaz, 2016; Larson et al, 2009; West & Bailey, 2012). Also in Stroop tasks, the amplitude of a subsequent component called the “frontal slow wave” (latency ~600-800 ms or later) is also sensitive to conflict and base rate (Bailey, West, & Anderson, 2010; West & Bailey, 2012).…”
Section: Introductionmentioning
confidence: 99%
“…The MFN/N450 peaks at ~450 ms in visual Stroop tasks (Tillman & Wiens, 2011; West & Bailey, 2012). It shows both base rate and sequence effects and is thought to reflect conflict monitoring (Cespón, Galdo-Álvarez, & Díaz, 2016; Larson et al, 2009; West & Bailey, 2012). Also in Stroop tasks, the amplitude of a subsequent component called the “frontal slow wave” (latency ~600-800 ms or later) is also sensitive to conflict and base rate (Bailey, West, & Anderson, 2010; West & Bailey, 2012).…”
Section: Introductionmentioning
confidence: 99%
“…It has also been shown that the age-related behavioral was related to N2pc and N2cc subcomponent during visual search task ( 23 ). The N2pc was found to play a role in visuospatial processing of target stimuli and the control of non-target stimuli, and the N2cc was also correlated to inhibition of spatial response tendencies in the Simon task ( 25 ). Another similar biomarker, the anterior contralateral N2 subcomponent (N2ac) has been shown to predict sound localization performance and diffusion model parameters using multiple linear regression 5,26 ).…”
Section: Introductionmentioning
confidence: 94%
“…Moreover, researchers have reported that the N2cc deflected over central electrodes sites might coincide in time with the N2 posterior contralateral (N2pc), but the important finding of N2cc is not due to overlap of the N2pc with movement execution-related activity ( 14,22 ). The other hand, the anterior contralateral N2 subcomponent (N2ac) appears in order to regulation sound localization performance 7,24 ) and also emerges in the visual Simon task and ( 25 ).…”
Section: Introductionmentioning
confidence: 99%
“…We examine the capacity of four prominent psychological scales (conscientiousness, need for cognition, locus of control, and delay of gratification) to explain real effort provision. Participants performed three different tasks: the Slider (Gill & Prowse, 2012), AX (Gonthier, Macnamara, Chow, Conway, & Braver, 2016) and Simon tasks (Cespón, Galdo-Álvarez, & Díaz, 2016) in two conditions. In the extrinsic motivation condition, they were offered material incentives and in the intrinsic motivation condition, performance was not linked to rewards.…”
Section: Background and Motivationmentioning
confidence: 99%
“…If participants saw the letter "A" followed by the letter "X" (or the sequence A -X), they were instructed to press the blue key on their keyboard, if they saw any other sequence, they were told to press the orange key. 4 The "Simon Task" is a cognitive psychology task focused on inhibition and attention (Cespón, Galdo-Álvarez, & Díaz, 2016). In this task, participants saw an arrow on their computer screen, pointing either left or right.…”
Section: Experimental Designmentioning
confidence: 99%